Chapter 4 Shirota Suzuko The victim-survivor-activist - Tsukamoto, Sachiyo (Taylor & Francis, 2022)
"The Politics of Trauma and Integrity uses the lenses of gender and trauma to tell the stories of narratives testified by two contrasting Japanese "comfort women" survivors. Through an innovative interdisciplinary study of the politics of gendered memory and trauma in historical context, with numerous primary sources for analysis including diaries, interviews, letters and oral testimonies, this book uncovers the life-or-death struggles of Japanese survivors in pursuit of public recognition as the victims of state violence against women. It is set within a gender history of modern Japan, supplemented by feminist activist methodology premised upon political agency that seeks social justice. The author's analysis draws upon three key concepts: trauma, coherence of the self, and integrity. Focusing upon the role of gender and trauma as the nexus between memory construction and identity formation in modern Japan, the author reveals these women's relentless quest for their recovery and creation of new identities. This book provides a better understanding of the victims of sexual violence and encourages readers to listen to the voice of trauma, as well as making a significant contribution to the existing research on the ongoing history of sexual violence against women in Japan, the rest of Asia and beyond. It will be of interest to scholars, researchers, activists and all who are interested in the issue of women's human rights. It provides supplementary reading and research material for history and politics courses relating to Japan and East Asia, memory, identity, trauma, gender, war and feminist activism. This book will also be beneficial to victims of sexual violence as well as the counsellors/psychologists engaging with them."